Treatment of progressive multifocal leukoencephalopathy–immune reconstitution inflammatory syndrome with intravenous immunoglobulin in a patient with multiple sclerosis treated with fingolimod after discontinuation of natalizumab. Issue 3 (March 2015) - Calic, Z.; Cappelen-Smith, C.; Hodgkinson, S.J.; McDougall, A.; Cuganesan, R.; Brew, B.J.
Abstract We report a case of progressive multifocal leukoencephalopathy–immune reconstitution inflammatory syndrome in a multiple sclerosis (MS) patient 3.5 months after fingolimod commencement and 4.5 months after natalizumab (NTZ) cessation. Three cerebrospinal fluid analyses were required before a definitive diagnosis of progressive multifocal leukoencephalopathy was reached. Intravenous immunoglobulin (IVIG) was subsequently given as the sole MS treatment along with mirtazapine and mefloquine. There has been improvement and subsequent clinical stabilization. The notable features are the difficult timing of fingolimod commencement in the context of previous NTZ therapy, the role of repeated cerebrospinal fluid John Cunningham virus analyses in progressive multifocal leukoencephalopathy diagnosis, and the role of IVIG.